2008
DOI: 10.1002/cbm.701
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Beck Depression Inventory‐II with incarcerated male offenders aged 18–21 years

Abstract: The BDI-II showed good internal consistency and concurrent validity. Factor analysis revealed two factors, relating to cognitive-affective items and somatic items. The items loading on the two factors were very similar to those found in a North American adolescent (13-17 years) psychiatric inpatient sample. CONCLUSIONS AND IMPLICATIONS FOR FUTURE RESEARCH: The findings suggest that the BDI-II can be used with confidence in young adult male offenders. It would be useful to confirm its psychometric properties in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…In these studies, the two factors were named cognitiveÁaffective and somatic concerns. In general, our results concur with the EFA results from a number of other studies identified in the literature (e.g., Palmer & Binks, 2008;Penley, Wiebe, & Nwosu, 2003;Storch, Roberti, & Roth, 2004;Whisman, Perez, & Ramel, 2000;VanVoorhis & Blumentritt, 2007).…”
Section: Discussionsupporting
confidence: 94%
“…In these studies, the two factors were named cognitiveÁaffective and somatic concerns. In general, our results concur with the EFA results from a number of other studies identified in the literature (e.g., Palmer & Binks, 2008;Penley, Wiebe, & Nwosu, 2003;Storch, Roberti, & Roth, 2004;Whisman, Perez, & Ramel, 2000;VanVoorhis & Blumentritt, 2007).…”
Section: Discussionsupporting
confidence: 94%
“…The BDI-II had a high level of internal consistency (Cronbach's a = .90). Furthermore, the study found convergent validity, which was evident from the significant correlation between the BDI-II and BHS (r = .55, p < .001; Palmer & Binks, 2008). Boothby and Durham (1999) confirmed that women and younger offenders report higher scores on the BDI-II, which supported the view that mild and severe depression are more evident among women offenders.…”
Section: Beck Depression Inventory-2nd Edition (Bdi-ii)supporting
confidence: 73%
“…A similar two-dimensional structure was obtained in nonclinical samples using a different language version of the BDI-II, 27,31,55 in psychiatric samples, 8,33,55,62,65,82,88,91 and in medical patients. 96,114,116,124 The between-factor correlation coefficients in the two-dimensional structure of the BDI-II were generally high (.…”
Section: Content and Construct Validitysupporting
confidence: 63%